2021
DOI: 10.1101/2021.01.31.429053
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning and attention increase visual response selectivity through distinct mechanisms

Abstract: Selectivity of cortical neurons for sensory stimuli can increase across days as animals learn their behavioral relevance, and across seconds when animals switch attention. While both phenomena are expressed in the same cortical circuit, it is unknown whether they rely on similar mechanisms. We imaged activity of the same neuronal populations in primary visual cortex as mice learned a visual discrimination task and subsequently performed an attention switching task. Selectivity changes due to learning and atten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 73 publications
2
15
0
Order By: Relevance
“…Similar to BCI training, a substantial fraction of V1 neurons retained their tuning preference after visual discrimination training, when probed outside of the training environment. It was previously observed that during a similar implementation of the visual discrimination task used here, activity during task execution was slightly depressed 50 , selectivity for the stimuli used during training increased in a context-dependent manner 16 , and selective suppression dominated when the animals were engaged in the task 51 . Our results are consistent with these previous observations, considering our measurements were made outside of the training environment and therefore can also be considered a different context.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Similar to BCI training, a substantial fraction of V1 neurons retained their tuning preference after visual discrimination training, when probed outside of the training environment. It was previously observed that during a similar implementation of the visual discrimination task used here, activity during task execution was slightly depressed 50 , selectivity for the stimuli used during training increased in a context-dependent manner 16 , and selective suppression dominated when the animals were engaged in the task 51 . Our results are consistent with these previous observations, considering our measurements were made outside of the training environment and therefore can also be considered a different context.…”
Section: Discussionmentioning
confidence: 51%
“…The BCI task used in this study was multimodal in nature. To determine whether our results generalize to a single-modality task, we trained mice in a visual discrimination task in which it was previously established that V1 activity is required for improved behavioral performance 16,50,51 . Converging evidence indicates visual discrimination training enhances the neural representation of rewarded stimuli by increasing selectivity for the stimuli experienced during training 16,21 and in some cases improving response reliability 16 , and at the same time suppresses responses to non-relevant stimuli 16 .…”
Section: Stimulus Information Was Maintained After Learning a Visual ...mentioning
confidence: 99%
“…Furthermore, stimulus representations evolve as animals learn, even in primary sensory cortices. One might expect that after learning, the number of neurons selective for behaviorally-important stimuli increases, as has been observed in auditory (5,6), somatosensory (7,8), and visual cortex (9,10). Other studies, however, have found a paradoxical decrease in the number of cortical neurons responding optimally to learned stimuli (11,12), and in primary visual cortex (V1), neurons increase their slope at the task stimulus in a manner dependent on orientation preference (13).…”
mentioning
confidence: 89%
“…Details of the experiment, data preprocessing, calculation of behavioral d-prime (Figure 3B), and fitting and validation of MVAR model on this dataset data have been described in detail in previous publications (Khan et al, 2018; see also Poort et al, 2015Poort et al, , 2021. Here, we summarize the MVAR model and provide details of novel MVAR analyses used in the present study.…”
Section: Methods Detailsmentioning
confidence: 99%